How Does AI Support Surgical Skills Assessment? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
The landscape of surgical training is undergoing a significant transformation, driven by the integration of artificial intelligence (AI). Traditionally, the ...
Keywords: AI in Surgery and Robotics; Support; Surgical; Skills; Artificial Intelligence; Machine Learning; Deep Learning